Effect of Enterococcus faecalis OG1RF on human calvarial osteoblast apoptosis - Yang Li; Shuyu Sun; Cheng Wen; Jialin Zhong; Qianzhou Jiang (BMC, 2022)
Abstract Background Enterococcus faecalis is a dominant pathogen in the root canals of teeth with persistent apical periodontitis (PAP), and osteoblast apoptosis contributes to imbalanced bone remodelling in PAP. Here, we investigated the effect of E. faecalis OG1RF on apoptosis in primary human calvarial osteoblasts. Specifically, the expression of apoptosis-related genes and the role of anti-apoptotic and pro-apoptotic members of the BCL-2 family were examined. Methods Primary human calvarial osteoblasts were incubated with E. faecalis OG1RF at multiplicities of infection corresponding to infection time points. Flow cytometry, terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) assay, caspase-3/-8/-9 activity assay, polymerase chain reaction (PCR) array, and quantitative real-time PCR were used to assess osteoblast apoptosis. Results E. faecalis infection increased the number of early- and late-phase apoptotic cells and TUNEL-positive cells, decreased the mitochondrial membrane potential (ΔΨm), and activated the caspase-3/-8/-9 pathway. Moreover, of all 84 apoptosis-related genes in the PCR array, the expression of 16 genes was upregulated and that of four genes was downregulated in the infected osteoblasts. Notably, the mRNA expression of anti-apoptotic BCL2 was downregulated, whereas that of the pro-apoptotic BCL2L11, HRK, BIK, BMF, NOXA, and BECN1 and anti-apoptotic BCL2A1 was upregulated. Conclusions E. faecalis OG1RF infection triggered apoptosis in human calvarial osteoblasts, and BCL-2 family members acted as regulators of osteoblast apoptosis. Therefore, BCL-2 family members may act as potential therapeutic targets for persistent apical periodontitis.